Cx601 (darvadstrocel) for the treatment of perianal fistulizing Crohn's disease. (3rd July 2019) - Bislenghi, G.; Wolthuis, A.; Van Assche, G.; Vermeire, S.; Ferrante, M.; D'Hoore, A.
ABSTRACT: Introduction : Given the well-documented difficulty to treat perianal fistulizing Crohn's disease (pCD), with 40% of patients experiencing recurrence even after reiterative surgery and advanced medical therapy, research in this field has focused on the role of mesenchymal stem cells (MSC). Areas covered : The aim of this article is to furnish an overview of the pathogenetic mechanisms, clinical applications and evidences for the use of MSC for pCD with particular focus on adipose-derived allogenic MSC including darvadstrocel. Expert Opinion : The effect of MSC on fistula healing is probably mediated by their anti-inflammatory properties more than by their ability to engraft and trans-differentiate in the healthy tissue. A holistic treatment of pCD, addressing different pathophysiological factors, may represent the key for an improvement in the healing rate. In this setting, MSC might play a role as 'augmentation' therapy in combination with more conventional treatments. Whether MSC have benefit in non-complex fistula in biological naïve patients, in complex fistula with many tracts and/or in rectovaginal fistulas, are unexplored fields that need further investigation. A central registry of pCD patients undergoing treatment with MSC should be created in order to elucidate the efficacy, safety and costs of stem cells treatment on long term follow up.